2023
DOI: 10.1136/bmjsem-2022-001486
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity and tolerability of two high-intensity interval training protocols in patients with COPD: a randomised cross-over pilot study

Abstract: ObjectivesHigh-intensity interval training (HIIT) during pulmonary rehabilitation in patients with chronic obstructive pulmonary disease (COPD) may alleviate the symptom burden, but the fidelity and tolerability of HIIT using long or short intervals in patients with COPD are unknown.MethodsTwelve patients with moderate-to-severe COPD were included in a randomised cross-over pilot study. They completed two supervised HIIT protocols (4×4 and 10×1). To compare the two HIIT protocols, completed training amount, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Due to the low-risk intervention with supervised HIIT exercise [ 50 , 64 ] in a low-risk study population (no severe liver disease indicated by no cirrhosis/liver cancer or antiviral treatment, no coronary heart disease, no pregnancy), a data monitoring committee was not formed.…”
Section: Oversight and Monitoringmentioning
confidence: 99%
“…Due to the low-risk intervention with supervised HIIT exercise [ 50 , 64 ] in a low-risk study population (no severe liver disease indicated by no cirrhosis/liver cancer or antiviral treatment, no coronary heart disease, no pregnancy), a data monitoring committee was not formed.…”
Section: Oversight and Monitoringmentioning
confidence: 99%